THE EFFECT OF VOLUNTARY DISCLOSURE PROGRAM (VDP) AND TAXPAYER AWARENESS ON INDIVIDUAL TAXPAYER COMPLIANCE - Adrian, Rebecca Nicole; Muid, Dul (Diponegoro Journal of Accounting, 2024)
This study aims to examine and analyze the effect of voluntary disclosure programs and taxpayer awareness on individual taxpayer compliance at Tax Office Candisari Semarang. This research was conducted by quantitative methods. Data obtained as primary data, through a questionnaire. The sample studied was 100 individual taxpayers in Semarang. The sampling technique uses purposive sampling. Data analysis is carried out by descriptive statistical analysis, data quality test, classical assumption test, multiple linear regression analysis, and model validity test using SPSS version 26. The results showed that (a) voluntary disclosure program has a significant positive effect on individual taxpayer compliance, (b) taxpayer awareness has a significant positive effect on individual taxpayer compliance.